2015
DOI: 10.1093/scan/nsv128
|View full text |Cite
|
Sign up to set email alerts
|

Differential serotonergic innervation of the amygdala in bonobos and chimpanzees

Abstract: Humans' closest living relatives are bonobos (Pan paniscus) and chimpanzees (Pan troglodytes), yet these great ape species differ considerably from each other in terms of social behavior. Bonobos are more tolerant of conspecifics in competitive contexts and often use sexual behavior to mediate social interactions. Chimpanzees more frequently employ aggression during conflicts and actively patrol territories between communities. Regulation of emotional responses is facilitated by the amygdala, which also modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 90 publications
(114 reference statements)
1
53
0
Order By: Relevance
“…Stimpson et al. () has identified an evolutionary change in the serotonergic innervation of the amygdala between chimpanzees and bonobos, and suggested that it has led to differences in the aggressive behaviors, cautious temperaments, risk preferences, and performances on “theory of mind” tasks even between these closely related species. Raghanti et al.…”
Section: Resultsmentioning
confidence: 99%
“…Stimpson et al. () has identified an evolutionary change in the serotonergic innervation of the amygdala between chimpanzees and bonobos, and suggested that it has led to differences in the aggressive behaviors, cautious temperaments, risk preferences, and performances on “theory of mind” tasks even between these closely related species. Raghanti et al.…”
Section: Resultsmentioning
confidence: 99%
“…Bonobos have more gray matter than do chimpanzees in brain regions thought to be concerned with empathy and social cognition . In bonobos, the amygdala, an area of the brain that regulates emotional responses, social decision making, memory, and attention, is larger and has more serotonic innervation than that in chimpanzees …”
Section: The Role Of Pan In Models Of Hominin Evolutionmentioning
confidence: 99%
“…This hypothesis is supported by data revealing a syndrome of behavioral, morphological, and psychological traits in bonobos that are similar to those found in artificially domesticated species. The cooccurrence of these traits in bonobos and domesticated species is thought to result from selection (natural or artificial) against aggression, which has led to changes in developmental timing and neurophysiology, including alterations to the hypothalamic-pituitary-adrenal axis, androgen levels, and the serotonergic system (40,53).…”
Section: Becoming Humanmentioning
confidence: 99%
“…2). Comparative brain imaging studies with chimpanzees and bonobos also reveal that bonobos have more gray matter in regions implicated in empathy and more robust neural pathways relating to the inhibition of aggression (86), with bonobos having approximately twice the serotonergic innervation of the amygdala in comparison with chimpanzees (53).…”
Section: Becoming Humanmentioning
confidence: 99%